Smith's illustrated astronomy, designed for the use of the public or common schools in the United States: illustrated with numerous original diagrams - wydawca (Daniel Burgess & Co., 1854)
Centripetal and Centrifugal Forces s. 11.
by Asa Smith ; Daniel Burgess and Co.
Keywords: Teleskop; atlasy astronomiczne; Kartografia; Wenus (astr.); Astronomia; Merkury (astr.); Astronomia - urządzenia; Astronomowie; Niebo; Zaćmienia; Komety; Mgławice; Ziemia; Droga mleczna; Zodiak; Pory roku; Saturn (astr.); Jupiter (astr.); Planety; Mars (astr.); Gwiazdy; Księżyc; Słońce; Układ słoneczny; Świat; w kartografii; Lewiatan - teleskop; Rosse zob. Lewiatan